Detection of Antibiotic Residues in Broiler Meat by Thin Layer Chromatography - Thapa, Santosh; Acharya, Dev Raj; Dahal, Bibek; Khatri, Bishnu Bahadur; K.C., Yadav (KMC Journal, 2023)
Antibiotic usage has played a significant role in the growth of poultry industry all across the globe. But because of indiscriminate use of antibiotics, several incidences related to occurrence of antibiotic residues in broiler meat have been reported. In the context of Nepal, only limited studies have been attempted to assess the presence of antibiotic residues in poultry meat and thus this study aims to determine the same in Dharan. A questionnaire survey was conducted among poultry farmers and veterinary shops in Dharan where 44% of respondents had training on poultry farming but only 4 % had knowledge on antimicrobial resistance in microorganism. The survey report showed maximum usage of doxycycline and tetracycline in poultry farms. Four types of broiler meat, namely, liver, breast muscle, kidney and gizzard were collected and screening of antibiotic residues (ciprofloxacin, doxycycline, enrofloxacin, gentamycin and tetracycline) in them was performed by thin layer chromatography. On thin layer chromatography, 9%, 17%, 8%, 3% and 21% of samples were detected with ciprofloxacin, doxycycline, enrofloxacin, gentamycin and tetracycline residues respectively. Highest occurrence of ciprofloxacin, doxycycline, enrofloxacin and tetracycline residues were found in kidney (16%), gizzard (32%), liver (12%) and kidney (36%) samples respectively.